Adenovirus-associated anti-miRNA-214 regulates bone metabolism and prevents local osteoporosis in rats - Wang, Cheng; Wang, Peng; Li, Feng; Li, Yang; Zhao, Minwei; Feng, Hui; Meng, Haoye; Li, Junyang; Shi, Peng; Peng, Jiang; Tian, Hua (Frontiers in Bioengineering and Biotechnology, 2023)
Objective： We investigated the expression of miRNA-214 in human osteoporotic bone tissue and tested the utility of an adeno-associated virus (AAV) expressing an miRNA-214 inhibitor in terms of preventing local osteoporosis of the femoral condyle in a rat model of osteoporosis. Method: ① Femoral heads of patients who underwent hip replacements at our hospital because of femoral neck fractures were collected and divided into osteoporosis and non-osteoporosis groups based on preoperative bone mineral density data. MiRNA-214 expression was detected in bone tissues exhibiting obvious bone microstructural changes in the two groups. ②A total of 144 SD female rats were divided into four groups: Control, Model, Negative control (Model + AAV), and Experimental (Model + anti-miR214) groups. AAV-anti-miRNA214 was injected locally into rat femoral condyles; we explored whether this prevented or treated local osteoporosis. Results: ① Human femoral head miRNA-214 expression was significantly increased in the osteoporosis group. ② Compared to the Model and Model + AAV groups, the bone mineral density (BMD) and femoral condyle bone volume/tissue volume (BV/TV) ratio in the Model + anti-miR214 group were significantly higher, as were the number (TB.N) and thickness (TB.Th) of trabecular bones (all P < 0.05). MiRNA-214 expression in femoral condyles of the Model + anti-miR214 group was significantly higher than in the other groups. The expression levels of the osteogenesis-related genes Alp, Bglap, and Col1α1 increased, while those of the osteoclast-related genes NFATc1, Acp5, Ctsk, Mmp9, and Clcn7 decreased. Conclusion: AAV-anti-miRNA-214 promoted osteoblast activity and inhibited osteoclast activity in the femoral condyles of osteoporotic rats, improving bone metabolism and slowing osteoporosis progression.